2004
DOI: 10.1111/j.1365-294x.2004.02110.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of California coyotes corresponds to habitat‐specific breaks and illuminates species history

Abstract: Little is known about the relationship between animal movements and the emergent structure of populations, especially for species occupying large continuous distributions. Some such mammals disperse disproportionately into habitat similar to their natal habitat, a behavioural bias that might be expected to lead to habitat-conforming genetic structure. We hypothesized that coyotes (Canis latrans) would exhibit such natal-biased dispersal, and used 13 microsatellite loci to test, correspondingly, whether genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
163
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(174 citation statements)
references
References 34 publications
10
163
1
Order By: Relevance
“…Natal-habitat biased dispersal seems a possible explanation in the case of Carpathian wolves, and is consistent with findings from Europe and North America (Geffen et al 2004;Sacks et al 2004;Pilot et al 2006). Population genetic structure consistent with the presence of highland and lowland habitats has been reported in coyotes (Sacks et al 2004(Sacks et al , 2005 and merits further attention in wolf populations from the Carpathians Mountains and surrounding lowland areas. Differences in the legal status and protection of the species in the Carpathians might also influence genetic structure, as only wolves in the Polish and Czech parts of the north-western edge of the Carpathian Mountains are protected.…”
Section: Factors That Could Maintain Divisions Between Genetically DIsupporting
confidence: 70%
See 1 more Smart Citation
“…Natal-habitat biased dispersal seems a possible explanation in the case of Carpathian wolves, and is consistent with findings from Europe and North America (Geffen et al 2004;Sacks et al 2004;Pilot et al 2006). Population genetic structure consistent with the presence of highland and lowland habitats has been reported in coyotes (Sacks et al 2004(Sacks et al , 2005 and merits further attention in wolf populations from the Carpathians Mountains and surrounding lowland areas. Differences in the legal status and protection of the species in the Carpathians might also influence genetic structure, as only wolves in the Polish and Czech parts of the north-western edge of the Carpathian Mountains are protected.…”
Section: Factors That Could Maintain Divisions Between Genetically DIsupporting
confidence: 70%
“…The moderate F ST values (0.05-0.15) observed between a number of lowland regions require further investigation, as well as the high F ST value (0.156) seen between wolves in regions 6 and 7 that are separated by \50 km. Assessment of samples from contiguous regions, landscape features, and additional genetic markers could improve understanding of the extent to which these differences might be explained by landscape fragmentation or ecological differences resulting in natal habitat-biased dispersal (Geffen et al 2004;Sacks et al 2004;Pilot et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the two dingo populations have different ecological or biological characteristics relevant to the conservation and management of the species or its role in specific ecosystems. Patterns of genetic subdivision in other large carnivores have been linked to ecologically relevant characteristics such as neonatal dispersal (Sacks, Bannasch, Chomel, & Ernest, 2008; Sacks, Brown, & Ernest, 2004), prey specialization (Carmichael, Nagy, Larter, & Strobeck, 2001), environmental climes (Carmichael et al., 2001; Rueness, Jorde et al., 2003; Rueness, Stenseth et al., 2003; Stenseth et al., 2004), and sociality (Randall, Pollinger, Argaw, Macdonald, & Wayne, 2010). This is a key knowledge gap, which needs to be interrogated by future ecological research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Pilot et al (2006) found that genetic differentiation in European wolves was correlated with climate, habitat types, and diet composition and also suggested that natalhabitat biased dispersal was the underlying mechanism linking population ecology vntin genetic sb:xicture. Apparently, in large canids, ecotypic divergence may be the primary mode of differentiation (Carmichael et al 2001;Musiani 2003;Geffen et al 2004;Sacks et al 2004Sacks et al , 2005Pilot et al 2006;Carmichael et al in press) presenting an alternative to topographically induced population structure (Avise 2000).…”
Section: Prey-mediated Differentiation Of Tundra/taiga and Boreal Conmentioning
confidence: 99%